The effects of tanning on health - Irena Puszkarz; Jadwiga Bednarek; Ewa Dziarmaga (Kazimierz Wielki University, 2017)
Ultraviolet (UV) ray exposure can lead to serious consequences to a person(s) health. Consequences include skin pigmentation and can also lead to cancer. Not everyone however is aware of the risks involved with exposure to these rays. Lack of protection against these UV rays can lead to serious health consequences with a reported increase in skin cancer including melanoma.